THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN CHILDREN'S CHARACTER FORMATION - St. Wardah Hanafie Das; Nafsia Marasabessy; Sudirman Herman (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This research explores the fundamental role of Islamic Religious Education (IRE) as a strategic instrument in constructing noble character personalities in children amidst the dynamics of contemporary digital transformation. Utilizing a qualitative approach with a comprehensive literature review method, this study profoundly analyzes the mechanisms of internalizing Islamic values in the character formation process of the younger generation. The research findings indicate that Islamic Religious Education plays a vital role as a spiritual foundation in instilling principles of morality such as honesty (shiddiq), trustworthiness (amanah), intelligence (fathonah), and communicative ability (tabligh), which are integrated into both intracurricular and extracurricular learning. Essential Islamic character values include patience, integrity, empathy, responsibility, and discipline, which shape the students' holistic personality. Effective implementation in the digital era necessitates adaptive strategies that integrate learning technology with pedagogical approaches based on the values of the Qur'an and Hadith, through synergistic collaboration between educators, families, and the community. This study offers a theoretical contribution to the development of a contemporary Islamic education paradigm that is responsive to the challenges of modernity while maintaining the authenticity of Islamic teachings in forming a generation with noble character, high individual and social piety.Character Building